A Study on Psychological Impact of Working From Home of Employees during COVID-19 Pandemic- a Cross Sectional Study - Dondapati, Sumedha; S., Iniyan; B., Ajay; R., Maathanghi; P., Kavitha (Current Psychiatry Research and Reviews, 2025)
IntroductionWith the sudden onset of COVID-19, many organisations introduced a mandatory relocation of workforce from their workplace to their homes bringing in a work from home policy for their employees. The purpose of the study is to examine the positive and negative impact on quality of life of teleworking, thereby assessing the prevalence of psychological distress of employees working in COVID-19.MethodsA cross sectional study was conducted on Indian - representative survey of self-reported data through an online questionnaire of work from home employees and their responses were analysed using SPSS software.ResultsThe study findings revealed that out of 2943 total respondents to the questionnaires, 18.9% and 20.2% had agreed and strongly agreed respectively to the statement that, work from home was a chance to break old habits and change routine. The mean positive affect score among those affected with COVID was 20.82 ± 3.71 and for those not affected with COVID was 21.12 ± 3.71.ConclusionThe results indicate age disparities in mental distress, perceived adversities highlighted the discrepancies differed by the area of residence and those affected by the corona virus.
Keywords: Work from home